Current use of patient-reported outcome measures by musculoskeletal physiotherapists in Portugal - Santos, Ruben (2024)
BACKGROUND: Musculoskeletal conditions are the leading cause of disability, requiring continuous outcome measurement, including the utilization of patient-reported outcome measures (PROMs). OBJECTIVE: The aims of the study were a) to characterize the use PROMs by Portuguese physiotherapists in patients with musculoskeletal conditions; b) to analyze the associated factors of their use and; c) to identify the barriers and facilitators to their implementation. METHODS: A cross-sectional online survey was carried out with musculoskeletal physiotherapists working in Portugal. Closed questions were used to describe the use of PROMs. The factors associated with the non-use of PROMs were analysed through logistic regression models (p= 0.05). Barriers and facilitators were assessed through open questions and analyzed using thematic analysis. RESULTS: One hundred and fifty-six physiotherapists answered the online survey. Most physiotherapists do not use outcome measures consistently and physical tests are often chosen (70.5%) over PROMs (17.3%). The work sector (p= 0.01; p= 0.015; p= 0.009). the workplace stimulus (p= 0.001) and the physiotherapists' knowledge about PROMs (p= 0.017) were identified as factors associated with the non-use of PROMs. Barriers and facilitators to the use of PROMs are related to physiotherapists' skills, the patients' characteristics, the workplace conditions, and the instruments' characteristics. CONCLUSION: This study showed the poor use of PROMs by musculoskeletal physiotherapists and identified the associated factors, barriers, and facilitators that should be considered to increase its future use by musculoskeletal physiotherapists in Portugal.